The Role of Parents in Developing Aspects of Children's Language Development Through Digital Technology - Naura Shafwah; Navy Ana Saputri; Tsabita Muthmainnah (Interkoneksi: Journal of Computer Science and Digital Business, 2024)
This study highlights the crucial role of parents in facilitating children’s language development through the integration of digital technology. By analyzing parents’ interactions with technology, this study aims to deeply understand its impact on children’s language development and identify effective strategies to support this development. Involving parents in childcare in the digital era is an important aspect that needs to be understood comprehensively. The research approach involves observing how parents use technology in their daily interactions with their children. In addition, this study will explore concrete strategies that parents can adopt to ensure that technology is used positively to support children’s language skills. It is hoped that the results of this study will provide valuable insights, providing guidance for parents in facing the challenges and opportunities that arise in childcare in an increasingly digitalized era. The conclusions of this study are expected to make a significant contribution to the understanding of the role of technology in children’s language development and provide a basis for responsive parenting practices in this digital era.